METODE CERAMAH: KONSEP DAN APLIKASI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MA AL MUKMIN TEMBARAK - Abdullah Rosyid Abdussalam; Abdul Malik (Almustofa Journal of Islamic Studies and Research, 2025)
This study aims to examine the concept and implementation of the lecture method in the teaching of Islamic cultural history at MA Al Mukmin Tembarak. The lecture method in Islamic History and Culture (SKI) involves the teacher delivering material to students through direct oral narration in the classroom, often supplemented with various media tools, to enhance understanding and engagement. The goal is to help students not only grasp the subject matter but also apply the knowledge in their daily lives in line with Islamic principles. The lecture method is grounded in the teachings of QS. Al-Furqan, 25:63, which encourages a method of teaching that is intensive yet enjoyable, ensuring that learning becomes both effective and meaningful for students. This method, while traditional, is structured around a series of organized steps to ensure the delivery is comprehensive and structured. The lecture method itself consists of six distinct stages, each of which is essential for the process and is designed to be integrated into the learning activities. These stages guide the teaching process and ensure that students engage actively with the material, fostering a deeper understanding of Islamic culture and history. Through this approach, the study aims to evaluate the effectiveness of the lecture method in achieving the intended learning outcomes, particularly in terms of students' ability to internalize and live by the values taught in their SKI lessons.